Erythrocyte-binding antigens of Plasmodium falciparum are targets of human inhibitory antibodies and function to evade naturally acquired immunity. - Persson, K; Fowkes, F; McCallum, F; Gicheru, N; Reiling, L; Richards, J; Wilson, D; Lopaticki, S; Cowman, A; Marsh, K; Beeson, J (2013)
Abs that inhibit Plasmodium falciparum invasion of erythrocytes form an important component of human immunity against malaria, but key target Ags are largely unknown. Phenotypic variation by P. falciparum mediates the evasion of inhibitory Abs, contributing to the capacity of P. falciparum to cause repeat and chronic infections. However, Ags involved in mediating immune evasion have not been defined, and studies of the function of human Abs are limited. In this study, we used novel approaches to determine the importance of P. falciparum erythrocyte-binding Ags (EBAs), which are important invasion ligands, as targets of human invasion-inhibitory Abs and define their role in contributing to immune evasion through variation in function. We evaluated the invasion-inhibitory activity of acquired Abs from malaria-exposed children and adults from Kenya, using P. falciparum with disruption of genes encoding EBA140, EBA175, and EBA181, either individually or combined as EBA140/EBA175 or EBA175/EBA181 double knockouts. Our findings provide important new evidence that variation in the expression and function of the EBAs plays an important role in evasion of acquired Abs and that a substantial amount of phenotypic diversity results from variation in expression of different EBAs that contributes to immune evasion by P. falciparum. All three EBAs were identified as important targets of naturally acquired inhibitory Abs demonstrated by differential inhibition of parental parasites greater than EBA knockout lines. This knowledge will help to advance malaria vaccine development and suggests that multiple invasion ligands need to be targeted to overcome the capacity of P. falciparum for immune evasion.